PtrHAT22, as a higher hierarchy regulator, coordinately regulates secondary cell wall component biosynthesis in Populus trichocarpa. (March 2022) - Ren, Mengxuan; Zhang, Yang; Wang, Ruiqi; Liu, Yingying; Li, Meiliang; Wang, Xueying; Chen, Xuebing; Luan, Xue; Zhang, Huaxin; Wei, Hairong; Yang, Chuanping; Wei, Zhigang
Highlights: A transcription factor was identified, PtrHAT22, from Populus trichocarpa, which was predominantly expressed in developing xylem, and evidenced to acts as a nuclear-localized transcription repressor. We for the first time identified the biological function of PtrHAT22 involved in SCW formation. As far as we known that similar effects of PtrHAT22 on SCW have not been found in other known wood-associated TFs, such as NAC and MYB TFs. The PtrHAT22, as a first hierarchy TF like PtrWNDs, is an upstream regulon of master switch PtrMYB20 and coordinately regulates SCW component biosynthesis through directly or indirectly controlling lower hierarchy TFs and structural genes of SCW formation network. Abstract: Homeodomain-leucine zipper (HD-Zip) II transcription factors ( TFs ) have been reported to play vital roles in diverse biological processes of plants. However, it remains unclear whether HD-Zip II TFs regulate secondary cell wall (SCW) in woody plants. In this study, we performed the functional characterization of a Populus trichocarpa HD-Zip II TF, PtrHAT22, which encodes a nuclear localized transcription repressor predominantly expressing in secondary developing tissues. Overexpression of PtrHAT22 showed arrested growths, including reduced heights and diameters above the ground, small leaves, and decreased biomass. Meanwhile, the contents of lignin, cellulose, and thickness of SCW significantly decreased, whilst the content of hemicellulose obviously increased in PtrHAT22 transgenic poplar. The expressions of some wood-associated TFs and structural genes significantly changed accordingly with the alternations of SCW characteristics in PtrHAT22 transgenic poplar. Furthermore, PtrHAT22 directly repressed the promoter activities of PtrMYB20, PtrMYB28, and PtrCOMT2, and bind two cis -acting elements that were specifically enriched in their promoter regions. Taken together, our results suggested that PtrHAT22, as a higher hierarchy TF like PtrWNDs, exerted coordination regulation of poplar SCW component biosynthesis through directly and indirectly regulating structural genes and different hierarchy TFs of SCW formation network.